Examining brand loyalty from an attachment theory perspective - Ofori, K.S.; Boateng, H.; Kosiba, J.P.; Adam, D.R.; Okoe, A.F. (Marketing Intelligence & Planning, 2020)
Purpose This study aimed to ascertain the relationship between experiential value, brand attachment and brand loyalty. The authors employed the attachment theory as the theoretical framework and operationalised attachment as a two-dimensional construct: identity-based and bonding-based. The authors argue that experiential value reinforces customer attachment in these two perspectives of attachment and consequently determine brand loyalty. Design/methodology/approach The authors used a survey research design and collected data from 500 customers of mobile telecommunication network companies in Ghana. The authors analysed the data collected using the partial least squares approach to structural equation modeling. Findings The findings of the study showed that there is a relationship between experiential value, brand attachment (identity-based and bonding-based) and brand loyalty. This study showed how experiential value reinforces each dimension of the attachment theory, and drives brand loyalty. Originality/value This study intensifies the application of attachment theory in the marketing literature. It provides insight into how brand loyalty is developed via attachment.
Research Article
Keywords: Service brand; Experiential value; Attachment theory; Bonding-based attachment; Identity-based attachment